Sistem pendukung keputusan dalam penentuan guru yang memenuhi kriteria sertifikasi nasional :: Studi kasus sertifikasi guru SMP Negeri 16 Surabaya - YULIUS, Abednego ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Decision Support System is an application program which can be used to determine which teachers are qualified and thus, will pass the national certification process. Assesment of the certification candidates is modelled based on their curriculum vitae, which include the latest formal dgree, the number of educations and trainings taken, teaching experiences, academic achievements, the number of publications, assesment by the previous employer, and involvement in some academic and/or social oraganizations. This novel invented system is capable of producing an assesment towards the certification candidates. It will further result in a pass or fail decision. The decision is produced based on the final evaluation result of the certification process by the system. This system is expected to assists in making a pass or fail decision for the certification team to determine which teachers fulfill the national certification area.